Compliance to prescribed medication among patients in a tertiary care hospital using Morisky-Green test - Manasa, Megaravalli R.; Preethy, Josephine Kennedy; Sachin, Idoor D. (International Journal of Basic & Clinical Pharmacology, 2016)
Background: Compliance to medication is an important factor in the success of any treatment. It also reduces the health care cost. The objective of the study was to examine compliance of patients to treatment and investigate reasons for such compliance and to quantify non adherence to medications and raise awareness about such factors. Methods: A prospective cross sectional questionnaire based study was conducted in 300 patients during three month period in 2013. The inclusion criteria was patients aged >18 years of both sexes and on treatment for diseases like asthma, hypertension, diabetes and coronary artery disease. Compliance was assessed using Morisky-Green test. Data was analysed by SPSS 19 and Chi square test was used to analyse the contingency tables and P ≤ 0.05 was considered significant. Results: The study revealed a compliance of 40.7%. There was statistically significant association between compliance and younger age, lower level of education, low socio-economic status, acute disease and presence of comorbidity. The common causes for non-compliance were forgetfulness and side effects of drugs. Conclusions: More than half of the study subjects were non-compliant. Hence a conscious effort is needed to educate the patients regarding their disease and the importance of compliance to treatment.